2019
DOI: 10.1002/acm2.12520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dosimetric uncertainty caused by MR geometric distortion in MRI‐based liver SBRT treatment planning

Abstract: Purpose MRI‐based treatment planning is a promising technique for liver stereotactic‐body radiation therapy (SBRT) treatment planning to improve target volume delineation and reduce radiation dose to normal tissues. MR geometric distortion, however, is a source of potential error in MRI‐based treatment planning. The aim of this study is to investigate dosimetric uncertainties caused by MRI geometric distortion in MRI‐based treatment planning for liver SBRT.Materials and MethodsThe study was conducted using com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Using population‐based HUs on five tissue segments resulted in a mean difference of 0.1% for target coverage according to our previous study . The dosimetric uncertainty caused by MRI geometric distortion only was ~0.5% when the distortion was 3 mm . Therefore, the combined uncertainty of distortion, segmentation accuracy, and population‐HU assignment is estimated to be ~0.6%.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Using population‐based HUs on five tissue segments resulted in a mean difference of 0.1% for target coverage according to our previous study . The dosimetric uncertainty caused by MRI geometric distortion only was ~0.5% when the distortion was 3 mm . Therefore, the combined uncertainty of distortion, segmentation accuracy, and population‐HU assignment is estimated to be ~0.6%.…”
Section: Discussionmentioning
confidence: 75%
“…19 The dosimetric uncertainty caused by MRI geometric distortion only was~0.5% when the distortion was 3 mm. 22 Therefore, the combined uncertainty of distortion, segmentation accuracy, and population-HU assignment is estimated to be~0.6%. This result indicates that the dosimetric accuracy is clinically acceptable and demonstrates the potential of using MRI alone for treatment planning in the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…The dosimetric impact of MR geometric inaccuracy for stereotactic radiation therapy has been evaluated and reported in previous studies [34,35]. In these studies, the MR geometric inaccuracy was rep- These results suggested the importance to assess dosimetric impact of the MR geometric inaccuracies during motion especially for regions of interest lying within a relatively large FOV since the magnitude of system related geometric inaccuracies increases with growing radial distance from the scanner's isocenter.…”
Section: Discussionmentioning
confidence: 92%
“…The dosimetric impact of MRI system-related inaccuracies has been evaluated and reported in the literature [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. These evaluations were performed using either images issued from real patients or images issued from digital phantoms.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al. ( 28 ) simulated a 2.77 mm average geometric distortion of the MRI with a phantom, and the average dose uncertainties for the target volumes and critical structures were small. The average distortion of the GE Discovery-sim 750 was 2.82 mm, which is close to Han’s result; thus, small distortions have minimal impact on the dosimetry for the MRI systems.…”
Section: Discussionmentioning
confidence: 99%